A.A.V.V.: Virtue Jurisprudence, C. Farrelly & L.B. Solum (eds.), New York, Palgrave-MacMillan, 2011, 268 pp. - Massini Correas, Carlos I. (Universidad Nacional de Cuyo. Facultad de Filosofía y Letras. Instituto de Filosofía., 2014)

(untitled)
Fil: Massini Correas, Carlos I.. Universidad de Mendoza